Effectiveness of Preventive Vaccination against Hepatitis A in the Republic of Sakha (Yakutia) - G. G. Onishchenko; M. E. Ignat’eva; L. V. Budatsyrenova; M. I. Mikhailov; Г. Г. Онищенко; М. Е. Игнатьева; Л. В. Будацыренова; М. И. Михайлов (Problems of Particularly Dangerous Infections, 2016)
Objective of the study is to analyze the influence of vaccination against hepatitis A on the corresponding morbidity rates in the Republic of Sakha (Yakutia).Materials and methods: statistical data contained in the statutory forms of the State statistical reporting on infectious diseases and preventive vaccination against hepatitis A in Yakutia, dated 1992 to 2015.Results and conclusions. Following selective immunization of high-risk groups, performed during the last 14 years in the Republic of Sakha, the incidence of hepatitis A has decreased by 38 times. According to the results of 2015, registered were 15 cases of infection, the rate being 1.6 per 100 thousand of the population, which was below the national average by 2.8 times. Assessment of the long-term dynamics has demonstrated the impact of preventive vaccination on the epidemic process of hepatitis A. Morbidity rates fall down with the increment of the numbers of immunized persons. Effect of the vaccination among the age group of 7 to 14 years is especially strong. Цель. Изучение влияния вакцинации против гепатита А на уровень заболеваемости гепатитом А в Республике Саха (Якутия).Материалы и методы. Анализ статистических данных отчетных форм государственной статистической отчетности по инфекционной заболеваемости и проведению профилактических прививок против гепатита А с 1992 по 2015 год в Якутии.Выводы и результаты. В результате проводимых в течение последних 14 лет в Республике Саха (Якутия) селективной иммунизации групп риска, заболеваемость гепатитом А снизилась за этот период в 38 раз. По итогам 2015 г. на территории зарегистрировано 15 случаев, показатель составил 1,6 на 100 тыс. населения, что ниже среднероссийских показателей в 2,8 раза. Проведенный анализ многолетней динамики заболеваемости гепатитом А на территории Республики Саха (Якутия) установил влияние вакцинопрофилактики гепатита А на эпидемический процесс гепатита А. С увеличением числа привитых уменьшается уровень заболеваемости. Особенно выражен эффект от иммунизации среди ...